2018
DOI: 10.1016/j.athoracsur.2018.01.073
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Automated Suture Fastening Device in Minimally Invasive Aortic Valve Replacement

Abstract: In mAVR, the CK device was associated with reduced aortic cross-clamp time while providing equivalent clinical outcomes. Larger studies are needed to confirm the efficacy, safety, and cost-effectiveness of the CK device in minimally invasive aortic valve surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 24 publications
0
28
2
Order By: Relevance
“…In terms of intraoperative outcomes, CPB was reported to be significantly reduced in two studies, one reported no difference and the other was not recorded (Table ). On the other hand, all of the studies reported the application of an automated fastener shortened AXT.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of intraoperative outcomes, CPB was reported to be significantly reduced in two studies, one reported no difference and the other was not recorded (Table ). On the other hand, all of the studies reported the application of an automated fastener shortened AXT.…”
Section: Resultsmentioning
confidence: 99%
“…stroke and transient ischemic attack, PPI, or PVL 9,22,24,30,32 ) as well as length of intensive care unit (ICU) stay. 10,24,30,32 Conflicting evidence is presented regarding length of hospital stay: Plestis et al 24 reported a significant reduction whilst four other studies showed no difference in this outcome. 10,22,30,32 Additionally, two studies measured postoperative aortic valve gradient; in one study, this was significantly reduced in the Cor-Knot cohort, whilst the other reported no difference.…”
Section: Cor-knot In Aortic Valve Surgerymentioning
confidence: 99%
“…11,33 With respect to CPBT and AXT, four of the five studies independently found these times to be reduced by Cor-Knot, a finding that was further supported by a meta-analysis. 6,11,19,27,33,34 30 -RCT Perin et al 9 -PCS Wang et al 9 -RCS Morgant et al 10 -PCS Length of ICU stay No significant difference Lee et al 30 -RCT No significant difference Grapow et al 11 -RCS Plestis et al 24 -RCS Perin et al 19 -PCS Beute et al 32 -RCS Morgant et al 10 -PCS Abbreviations: AXT, aortic cross clamp time; AVR, aortic valve replacement; CPBT, cardiopulmonary bypass time; ICU, intensive care unit; MA, meta-analysis; MV, mitral valve; PCS, prospective cohort study; PPI, permanent pacemaker implantation; PVL, paravalvular leak; RCS, retrospective cohort study; RCT, randomized controlled trial.…”
Section: Cor-knot In Mitral Valve Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…al. 3 included 1 incident of stroke (1.9%), 2 incidents (3.8%) of renal failure, 17 incidents (33.0%) of new-onset atrial brillation, 3 incidents (5.7%) of permanent pacemaker insertions and 11 incidents (21.2%) of post-operative transfusion of blood products. Except for renal failure and permanent pacemaker insertions, all reported incidences of post-operative complications were higher or comparable to our study.…”
Section: Post-operative Outcomementioning
confidence: 99%